Public Service Performance of Civil Servants (PNS) at South Tondano District Office in Minahasa Regency - Natasha Katie Giroth; Marthinus Mandagi; Wilson Bogar (Journal of Social Science, 2022)
This study aims to analyze and explain the performance of civil servants' public services at the Tondano Selatan District Office, Minahasa Regency, based on indicators: (1) PNS professionalism in providing services correctly and correctly, (2) awareness or desire to help the community/customers and provide fast service, (3) attitudes/behaviors and respect for consumers, (4) approaching and trying to find out the wants and needs of consumers, (5) availability and condition of office facilities and infrastructure at the South Tondano District Office. This study used a qualitative method. Data sources are determined by purposive and snowball sampling, while data collection techniques include interviews, observations, and documents. The results of study revealed the service performance of civil servants at the South Tondano District Office was based on indicators are 1) PNS professionalism in providing services appropriately and correctly in terms of the capabilities possessed by civil servants being able to provide the best service, (2) Awareness or desire to help the community/customers and provide fast service in this case civil servants are demanded to have a high responsiveness to be able to be responsive in providing services to the community by referring to the SOP in the South Tondano District Office, (3) Attitudes/behaviors, and respect for consumers in this case civil servants in demand to uphold ethics and have a good personality and also be able to communicate well in providing services (4) Approach, and try to find out the wants and needs of consumers in this case civil servants are expected to be able to fulfill the service according to the wishes and needs of the community but still in accordance by the rules doesn't happen. (5) The availability and condition of office facilities and infrastructure in the South Tondano District are expected to be improved and equipped to support better services for public